Recovery of chronically lame dairy cows following treatment for claw horn lesions: a randomised controlled trial - Thomas, H.J.; Remnant, J.G.; Bollard, N.J.; Burrows, A.; Whay, H.R.; Bell, N.J.; Mason, C.; Huxley, J.N. (BMJ Publishing Group, 2016)
A positively controlled, randomised controlled trial (RCT) was undertaken to test recovery of cows with claw horn lesions resulting in lameness of greater than two weeks duration. Cows on seven commercial farms were mobility scored fortnightly and selected by lameness severity and chronicity. Study cows all received a therapeutic trim then random allocation of: no further treatment (trim only (TRM)), plastic shoe (TS) or plastic shoe and NSAID (TSN). Recovery was assessed by mobility score at 42 (±4) days post treatment by an observer blind to treatment group. Multivariable analysis showed no significant effect of treatment with an almost identical, low response rate to treatment across all groups (Percentage non-lame at outcome: TRM – 15 per cent, TS – 15 per cent, TSN – 16 per cent). When compared with results of a similar RCT on acutely lame cows, where response rates to treatment were substantially higher, it can be concluded that any delay in treatment is likely to reduce the rate of recovery, suggesting early identification and treatment is key. Thirty-eight per cent of animals treated in this study were lame on the contralateral limb at outcome suggesting that both hindlimbs should be examined and a preventive or if necessary a therapeutic foot trim performed when lameness is identified particularly if the duration of lameness is unknown.